Deception In Competitive Sports: A Multifaceted Exploration Of Causes, Methods, And Implications - Dr. Prasannakumaran K; Dr. Sunil Alphonse (Revista Electronica de Veterinaria, 1970)
Sports deception is still a widespread problem that goes beyond national, cultural, and historical borders, despite being frequently presented as a departure from the fundamentals of fair play. This paper examines the phenomenon of cheating in sports by exploring its underlying causes, methods, and consequences. Adopting a multidisciplinary approach, the study investigates the psychological, sociocultural, and economic factors driving athletes and stakeholders to engage in dishonest practices. The study classifies common cheating techniques and evaluates their wider consequences providing a scientific understanding of how communities and sports organizations might address this issue while maintaining sports' integrity.